Digital Marketing Strategies to Increase Customer Engagement in the E-commerce Era - Tri Hartiningsih; Susie Bandari; Rachmiyantono (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
The e-commerce era has significantly changed the way businesses interact with customers. Amidst increasingly fierce digital competition, customer engagement is one of the key factors determining the success of a brand. This article discusses various digital marketing strategies that are effective in increasing customer engagement in the e-commerce era. Using a literature approach and recent case studies, this article identifies strategies such as personalization, content marketing, social media interactions, and the use of technologies such as Artificial Intelligence (AI) and gamification as methods for creating a more immersive customer experience. This article also examines how the use of digital platforms and data analytics can maximize the potential for customer engagement, and reviews the challenges faced by companies in implementing these strategies. The findings of this article show that well-designed digital marketing can increase customer loyalty, extend the customer lifecycle, and increase conversions, making it a vital component for business success in the digital era. Keywords: E-commerce, Customer engagement, Social media marketing, Digital marketing strategy, Content marketing, Gamification, Customer experience, Artificial Intelligence (AI) in marketing